The Effectiveness Assessement of Coral Reef Management (Case Study : Marine Conservation Area (MPA) Biawak Island and Area, Indramayu District) - Mutiara Salsabiela; Sutrisno Anggoro; Hartuti Purnaweni (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
Utilization of coral reefs by destructive and not environmentally friendly as well as water pollution , making it be in a worrying condition .condition of coral reefs in 2012 on the Biawak Island, 45.4% were in good condition and the remaining 27.3% were in fairly good condition and 27.4% are in poor condition with the risk index of 2.96 to 3.84 (southern part of the Biawak island). Establishment of MPA is one alternative policies management and protection of coral reefs and marine life that live in it, so hope to protect coral reefs and marine environment from adverse impacts.This study aims to assess the effectiveness of the management of coral reefs in MPA Biawak island and it was conducted in November-December 2013. The effectiveness of the management of coral reefs in Biawak island using a scorecard (Coremap-II) which includes the biophysical aspects of coral reef habitat conditions, social-economic and governance.The results showed that the effectiveness of the management of coral reefs in the MPA Biawak island and obtained scores around 139 with a percentage rating of 73.52%, it means less effective management. Keywords : Effectiveness, Management, Coral Reef, MPA Biawak Island